Knowledge Management Model for Construction Design Consulting Companies - Nghiem Vu, Phan; Le, Tuan Vu (International Journal of Sustainable Construction Engineering and Technology, 2022)
An optimum design is critical for improving a construction project efficiency in its implementation phase. However, it is observed in Vietnam that in many construction projects, the design optimization process has not attracted reasonable attention; this process is often carried out in a perfunctory manner without a systematic approach, then the projectsâ€™ designs are often not optimized, leading to a reduction in their performance efficiency. This study presents a knowledge-based approach with knowledge management model developed to aid in the management of a construction project’s design process, based on the intelligent use of accessible corporate data and experience knowledge. Semi-structured interviews were conducted in three construction consulting companies with the goal of learning how the selected design solution process was executed in practice and gaining necessary knowledge for system identification and design of the suggested model. A Construction Design Knowledge Model was created, operated, and validated with consultancy construction experts. The developed Construction Design Knowledge Model was deemed an advanced tool for building design selection as a result of its ability to assist consulting firms in creating corporate information, making decision-making in a less subjective manner, and lowering reliance on personal knowledge. The system’s indicated advantages helped to increase construction design performance